Overexpression, purification and characterization of Aspergillus niger beta-glucosidase in Pichia pastoris - Kamaruddin, S.; Abu Bakar, F.D.; Illias, R.M.; Said, M.; Hassan, O.; Murad, A.M.A. (Penerbit Universiti Kebangsaan Malaysia, 2015)
This study describes the expression of β-glucosidase (BglA) from Aspergillus niger in Pichia pastoris, a methylotrophic yeast strain, under the regulation of an alcohol oxidase promoter. The heterologous expression of BglA was optimized in a shake flask. Optimal conditions were achieved using an initial cell density (OD600) of 4-5 and an inducer concentration of 2.5% methanol for 72 hours. A recombinant protein with a molecular weight of ~116 kDa was produced. This recombinant BglA has optimal activity at 60°C in sodium acetate buffer at pH 4. This enzyme is stable between pH 3.0-6.0 and retained more than 50% of its maximum activity at pH 6.0 after incubation at 60°C for 30 min. However, it lost almost 80% of its maximal activity at pH 7.0 under the same conditions. A thermostability assay of this enzyme revealed that BglA is relatively stable up to 60°C. This enzyme retained 50% of its original activity at 60°C but was completely inactive after incubation at 70°C for 30 min. BglA showed highest activity and specificity towards the synthetic substrate p-nitrophenol-β-Dglucopyranoside with a specific activity of 347.62 U mg-1 and a specificity constant of 466.19 mL mg-1s-1. BglA had a specific activity of 6.2 U mg-1 and a specificity constant of 6.01 mL mg-1s-1 for cellobiose.